Social linguistics and literacies ideology in discourses - Gee, James Paul (Routledge, Taylor & Francis Group, 2015)
"This fifth edition offers an overview of the sociocultural approaches to language and literacy that coalesced into the New Literacy Studies. It also introduces readers to a particular style of analyzing language-in-use-in-society and develops a distinctive specific perspective on language and literacy centered on the notion of "Discourses". It will be of interest to researchers, lecturers and students in education, linguistics, or any field that deals with language, especially in social or cultural terms."--Provided by publisher.